The European Narcolepsy Network (EU‐NN) database. (26th January 2016) - Khatami, Ramin; Luca, Gianina; Baumann, Christian R.; Bassetti, Claudio L.; Bruni, Oliviero; Canellas, Francesca; Dauvilliers, Yves; Del Rio‐Villegas, Rafael; Feketeova, Eva; Ferri, Raffaele; Geisler, Peter; Högl, Birgit; et al.
Summary: Narcolepsy with cataplexy is a rare disease with an estimated prevalence of 0.02% in European populations. Narcolepsy shares many features of rare disorders, in particular the lack of awareness of the disease with serious consequences for healthcare supply. Similar to other rare diseases, only a few European countries have registered narcolepsy cases in databases of the International Classification of Diseases or in registries of the European health authorities. A promising approach to identify disease‐specific adverse health effects and needs in healthcare delivery in the field of rare diseases is to establish a distributed expert network. A first and important step is to create a database that allows collection, storage and dissemination of data on narcolepsy in a comprehensive and systematic way. Here, the first prospective web‐based European narcolepsy database hosted by the European Narcolepsy Network is introduced. The database structure, standardization of data acquisition and quality control procedures are described, and an overview provided of the first 1079 patients from 18 European specialized centres. Due to its standardization this continuously increasing data pool is most promising to provide a better insight into many unsolved aspects of narcolepsy and related disorders, including clear phenotype characterization of subtypes of narcolepsy, more precise epidemiological data and knowledge on the natural history of narcolepsy, expectations about treatment effects, identification of post‐marketing medication side‐effects, and will contribute to improve clinical trial designs and provide facilities to further develop phase III trials.